2000
DOI: 10.1002/(sici)1096-9837(200003)25:3<239::aid-esp54>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian sand transport at the Lanphere Dunes, Northern California

Abstract: Aeolian sand transport was studied at the Lanphere Dunes, a coastal dune complex in northern California, by comparing slipface advance rates with transport predicted based on local wind data. The slipfaces of a 2Á5 m high transverse ridge and 10 m high parabolic dune were monitored over a period of three months to estimate sand discharge. The study was performed during the dry season, which has the maximum sand-driving potential. Over the three month study period, average sand discharge was 12Á5 m 3 per m widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Robertson-Rintoul (1990) used anemometers, wind vanes and smoke candles to study the flow of air over a parabolic dune in Scotland and identified crestal jets, closed eddies on the lee and windward slopes, and spiral vortices along the arms. Craig (2000) used stakes placed near the base of the slipface to monitor the migration rate of a relatively small (10 meters high) coastal parabolic dune in northern California and used the results to calculate the amount of aeolian sand transport. Wolfe and Lemmen (1999) measured the migration of an inland parabolic dune in Saskatchewan over a three-year period and combined this with a study of elevation changes using pins placed on the dunes.…”
Section: Introductionmentioning
confidence: 99%
“…Robertson-Rintoul (1990) used anemometers, wind vanes and smoke candles to study the flow of air over a parabolic dune in Scotland and identified crestal jets, closed eddies on the lee and windward slopes, and spiral vortices along the arms. Craig (2000) used stakes placed near the base of the slipface to monitor the migration rate of a relatively small (10 meters high) coastal parabolic dune in northern California and used the results to calculate the amount of aeolian sand transport. Wolfe and Lemmen (1999) measured the migration of an inland parabolic dune in Saskatchewan over a three-year period and combined this with a study of elevation changes using pins placed on the dunes.…”
Section: Introductionmentioning
confidence: 99%
“…Following Craig (2000), the impact threshold normal velocity v t was calculated at the anemometer height (z = 3 m) and at the focal height z f , which is on the order of 0.01 m for normal dune sand (Bagnold, 1941). The velocities are 5.88 m s − 1 at the anemometer height (3 m) and 3.26 m s − 1 at the focal height.…”
Section: Methodsmentioning
confidence: 99%
“…The focal height z f provides a reference level for calculating shear velocity u ⁎ from (Bagnold, 1941;Craig, 2000): where v(z a ) is the observed wind velocity at the anemometer height, z a (3 m), and v t (z f ) is the threshold normal velocity at the focal height.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the dynamics of parabolic dunes has focused on several key topics including: (i) dune distribution and morphology (Landsberg, 1956;Cooper, 1958;David, 1977David, , 1981Pye, 1982;Anton and Vincent, 1986;Pye, 1993;Wolfe and David, 1997); (ii) timing of past dune activity (Wolfe et al, 1995;David et al, 1999;Wolfe et al, 2000Wolfe et al, , 2001Arbogast et al, 2002;Forman and Pierson, 2003;Havholm and Running, 2005); (iii) rates of migration (Cooper, 1958;Pye, 1982;Anthonsen et al, 1996;David et al, 1999;Craig, 2000;Tsoar and Blumberg, 2002;Bailey and Bristow, 2004;Marín et al, 2005); (iv) internal structure (Bigarella, 1975;Halsey et al, 1990); and (v) contemporary processes (Robertson-Rintoul, 1990;Arens et al, 2004). Despite this progress, they do represent the best-studied type of dunes, and both their morphological and dynamic parameters are well understood (e.g.…”
mentioning
confidence: 99%